Moro love the ambivalence of representation - Tampol, Jhayvee Belo 1991- (2012)
"This study will seek to interrogate, examine and deconstruct the stigmatized representations of the Moro identities, lives and struggles in the films Zamboanga (1937), The Real Glory (1939), Badjao (1957) and Bagong Buwan (2001). I will look at how these audio-visual texts make representations of the Moro to legitimize the status quo and to favor the othering of the Moro. By using Vicente Rafael's (2000) concept of White Love, Homi Bhabha's (1994) ambivalence of colonial discourse and his application of Sigmund Freud's (1927) fetish, this study will endeavor to expose the contradictions embedded within the stereotypes of the Moro, how these stereotypes reflect the pseudo-superiority of the Filipinos over the Moros. This study will argue that the concept of Filipino nation is impossible. Drawing on Slavoj Zizek's (1993) enjoyment of the other, the Filipinos detest Moros' organization of their enjoyment, which is grounded upon their political and social ascendancy which began during the 13th century and their history of resistance against the colonizers. Thus, Moro Love functions the same as White Love, where the Filipinos have taken upon themselves to assume the moral duty to suppress and oppress the Moros as a toll for their unyielding resistance to the powers and ideology of the colonizers. Zamboanga (1937), The Real Glory (1939), Badjao (1957) and Bagong Buwan (2001) as colonial discourses serve the purpose of the Moro Love by unrepresenting the Moros through their representation."